In Richard Wright's native soon, the gaze of the white eye ironically selfblinding works as panopticon and makes the black go blind - Nasrin, Nipa (BRAC University, 2010)
In Native Son Richard Wright explains the causes of the psychological blindness of the Blacks and of the Whites, along with their results. Wright illustrates how the white gaze and ideology work as panopticon and force the Blacks into a pressured and dangerous state of mind while the media constantly portrays them as animalistic brutes. This conditioning bounds the Black to react violently or to become blind towards own existence. Unknowingly the Whites also get conditioned by their deep-seated racial prejudices, despite some rare good intentions. Mrs. Dalton’s blindness represents White inability to see Blacks as anything other than the White media-enforced-stereotypes. Richard Wright deliberately suggests that America is self blinding, seeking to address the symptoms of racism while remaining incognizant of reality. In Bigger’s blindness, like Sophocles, Wright connects the idea of ‘excessive pride’ and anger. Bigger is as blind to his potentials as of the duality of the reality. This blindness, of which all the Biggers are the victims, results from the constant attack of racist propaganda and racial oppression. The Whites willingly created this dual blindness by using their ideological gaze as panopticon in order to condition Black life accordingly and to negate Black existence totally.